An audit of morbidity and mortality associated with foreign body aspiration in children from a tertiary level hospital in Northern India - Aparna Williams; Christina George; Philips S Atul; Sherene Sam; Sharmishtha Shukla (Wolters Kluwer Medknow Publications, 2014)
Background: There is paucity of data regarding the morbidity and mortality of rigid bronchoscopy in children for foreign body (FB) retrieval from India. The aim was to audit data regarding anaesthetic management of rigid bronchoscopy in children and associated morbidity and mortality. Materials and Methods: Hospital records of all patients below 18 years of age undergoing rigid bronchoscopy for suspected FB aspiration (FBA) between January 1, 2002 and December 31, 2011 were audited to assess their demographic profile, anaesthetic management, complications, and postoperative outcomes. The children were divided into early and late diagnosis groups depending on whether they presented to the hospital within 24 hours of FBA, or later. Results: One hundred and forty children, predominantly male (75%), with an average age of 1-year and 8 months, presented to our hospital for rigid bronchoscopy during the study period. Majority of children presented in the late diagnosis group (59.29% vs. 40.71%). The penetration syndrome was observed in 22% of patients. Majority of patients aspirated an organic FB (organic: Inorganic FB = 3:1), with peanuts being the most common (49.28%). A significantly higher number of children presented with cough (P = 0.0001) and history of choking (P = 0.0022) in the early diagnosis group and crepitations (P = 0.0011) in the late diagnosis group. Major complications included cardiac arrest (2.1%), pneumothorax (0.7%), and laryngeal oedema (9.3%). The average duration of hospitalization in our series was 3.08 ± 0.7 days. Conclusions: Foreign body aspiration causes considerable morbidity, especially when diagnosis is delayed.